2013
DOI: 10.1039/c3cp50600b
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of structure and nature of the PdO–Pd transformation using in situ PDF and XAS techniques

Abstract: The PdO-Pd phase transformation in a 4 wt% Pd/Al2O3 catalyst has been investigated using in situ X-ray absorption spectroscopy (XAS) and in situ X-ray total scattering (also known as high-energy X-ray diffraction) techniques. Both the partial and total pair distribution functions (PDF) from these respective techniques have been analysed in depth. New information from PDF analysis of total scattering data has been garnered using the differential PDF (d-PDF) approach where only correlations orginating from PdO a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 39 publications
(47 reference statements)
3
48
0
Order By: Relevance
“…Even with higher noise, the d-PDF is consistent with the PDF of the sample C (pure PdO - Fig. 1c) and with the analysis using synchrotron data reported in the literature [6]. Moreover, from the decay of the d-PDF it is possible to estimate the structural coherence length of PdO particles using the spherical diameter calculation in PDFgui.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Even with higher noise, the d-PDF is consistent with the PDF of the sample C (pure PdO - Fig. 1c) and with the analysis using synchrotron data reported in the literature [6]. Moreover, from the decay of the d-PDF it is possible to estimate the structural coherence length of PdO particles using the spherical diameter calculation in PDFgui.…”
Section: Discussionsupporting
confidence: 61%
“…In this contribution we demonstrate the application of this method to investigate the structural properties of nanosized PdO phase distributed on the reducible Fe 2 O 3 support. Unlike d-PDF studies previously reported which were based on synchrotron data [4][5][6], we used a laboratory diffractometer to collect high energy X-ray diffraction data [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Excellent fitting of the Pd EXAFS data was achieved by considering only the contribution of Pd fcc phase with a distance of 0.273 nm (0.271 in bulk Pd) in accordance with a similar study for Pd/PdO on g-Al 2 O 3 (0.274 nm). [32] In the absence of oxygen (N 2 atmosphere), operando XANES experiments demonstrated that PdO almost fully decomposes to Pd at 600 8C, even if in close contact with CeO 2 (Figure 8 b). The equilibrium is reversed under dry conditions leading to the almost immediate reoxidation of 25 % Pd to PdO followed by a further slow increase during the following reaction time (Figure 8 c).…”
mentioning
confidence: 96%
“…1.2.11d), as shown in Fig. 6 [35]. Note that the curve-fitting of XANES spectra was conducted with the reference materials (PdO and Pd foil) in the range of the absorption edge energy, E 0 between À20 and +30 eV with a typical agreement of R-factors = 0.0002.…”
Section: State Of Pdmentioning
confidence: 99%